Quantum Field Theory on Curved Spacetime and Black Holes (2025)
This thesis presents a monograph based on some literature review about quantum field theory (QFT) in curved spacetime, with a special focus on the quantum effects that occurs on it and, mainly, in black holes. The relation between quantum mechanics and general relativity reveals insights into the behavior of quantum fields in non-flat spacetimes. The first section explores some aspects and principles of QFT, the significance of curved spacetime and general relativity foundations; looking for the way to combine both in search of some quantum effects in the universe and the implications for black hole physics. The second section delves into specific quantum effects that arise in curved spacetime, which are the purpose of the work, including the Schwinger effect, the Unruh effect, the Hawking radiation, the Superradiance effect and the Memory Burden effect. Each phenomenon is examined physically and mathematically, emphasizing their theoretical principles and physical interpretations, thereby illustrating how quantum fluctuations can lead to observable consequences in gravitational contexts and particles interpretations, as the particle creation/annihilation in black hole horizons. In this monograph, our aim is to understand theoretical predictions in astrophysics and cosmology, due to curved spacetime. This predictions underscore the necessity of integrating quantum field theory with general relativity to enhance our understanding of fundamental physics in extreme environments, such as those surrounding black holes. This work presents a base to exploring the implications of these quantum effects in cosmological scenarios and their relevance on future research and deepness into high-energy astrophysics and cosmology, as the observational data is growing up on this field.